2018
DOI: 10.1002/bjs.10869
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of classification of distal cholangiocarcinoma based on tumour depth

Abstract: ITT is an accurate approach for depth assessment in DCC. The four-tier ITT classification with cut-off points of 1, 5 and 10 mm seems to be a better T system than those in the seventh and eighth editions of the AJCC classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 23 publications
6
27
0
Order By: Relevance
“…However, specific cut‐off points for ITT in perihilar tumours were not sought. Interestingly, the cut‐off points of 1, 5 and 8 mm reported in the present study are similar to those in other studies of distal or extrahepatic cholangiocarcinoma. A C1 tumour (ITT less than 1 mm) was highly associated with intraductal growth type, well differentiated histological grade, rare microscopic neurovascular invasion and absence of nodal metastasis ( Table ); all of these factors are well known positive prognostic indicators.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, specific cut‐off points for ITT in perihilar tumours were not sought. Interestingly, the cut‐off points of 1, 5 and 8 mm reported in the present study are similar to those in other studies of distal or extrahepatic cholangiocarcinoma. A C1 tumour (ITT less than 1 mm) was highly associated with intraductal growth type, well differentiated histological grade, rare microscopic neurovascular invasion and absence of nodal metastasis ( Table ); all of these factors are well known positive prognostic indicators.…”
Section: Discussionsupporting
confidence: 88%
“…This revision relies on two findings by Hong and colleagues, that the obscure outer layer of the bile duct leads to an uncertain T assignment and the depth‐based T system was better able to stratify than the layer‐based system. The present authors previously analysed patients with distal cholangiocarcinoma, confirming the satisfactory prognostic discrimination of this depth‐based approach despite two problems associated with depth measurement: lack of evidence of reliability and measurability susceptible to the direction of section of resected specimens. Recently, a single study demonstrated the prognostic value of tumour depth in perihilar cholangiocarcinoma, but failed to propose a T system using tumour depth.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations